Analysis of the use of Renewable Energies in Colombia and the Potential Application of Thermoelectric Devices for Energy Recovery - Forero, Jorge Duarte; Hernandez, Brando; Orozco, Wilman; AcuÃ±a, Norberto; Wilches, MarÃa Jimena (International Journal of Energy Economics and Policy, 2019)
This study investigates the current situation of electricity generation from non-conventional renewable energy sources in Colombia (NCRES). In general, it was shown that Colombia has potential in renewable sources such as solar, wind, and biomass. However, barriers such as lack of human capital, policies focused on conventional technologies and high investment costs have impeded their growth. Although the development of these sources has been encouraged through Law 1715 of 2014, more policies and developments are needed to promote this type of NCRES. The use of thermoelectric devices (TED) can become a potential NCRES alternative, while the political and technological conditions improve in Colombia. Around the world, TEDs have allowed the recovery of waste heat in a variety of industrial applications and the automotive sector. They are allowing in the latter, not only the generation of electric power, but also the reduction in engine emissions. Besides, its characteristics have allowed it to be used for the generation of electric power, both in developed and developing countries. In this document, an example presentation is developed that demonstrates the applications of the TED in the cases above to demonstrate the potential that the TED can have in almost any place that has a heat source. Keywords: Electricity Generation, Energy Policy, Energy Recovery, Non-conventional Renewable Energy, Thermoelectric Device JEL Classifications: L78, L90, O31, Q20 DOI: https://doi.org/10.32479/ijeep.8038